The intermediate care unit as a cost-reducing critical care facility in tertiary referral hospitals: a single-centre observational study - Plate, Joost D J (BMJ Open, 2019)
OBJECTIVES: To determine whether and to what extent the surgical intermediate care unit (IMCU) reduces healthcare costs. DESIGN: Retrospective cohort study. SETTING: The mixed-surgical IMCU of a tertiary academic referral hospital. PARTICIPANTS: All admissions (n=2577) from 2012 to 2015. PRIMARY AND SECONDARY OUTCOME MEASURES: The outcome measure was the hypothetical cost savings due to the presence of the IMCU. For this, each admission day was classified as either low-acuity or high-acuity, based on the Therapeutic Intervention Scoring System-28, the required specific nursing interventions and the indication for admission at the IMCU. Costs (2018) used were €463 per hospital ward, €1307 per IMCU and €2224 per intensive care unit (ICU) admission day. Savings were calculated by subtracting the actual IMCU costs from the hypothetical costs in the absence of the IMCU. RESULTS: There were 9037 admission days (n=2577 admissions) at the IMCU. The proportion of high-acuity admissions was 87.6%. Total costs at the IMCU were €11.808 888. Total hypothetical costs in absence of the IMCU were €18.115 284. Total cost savings were thus €6.306 395, or €1.576 599, per year. CONCLUSIONS: The surgical IMCU may substantially reduce societal healthcare costs, making it a cost saving alternative to ICU care. Constant adequate triage is essential to optimise its potential.